Real interest rates and population growth across generations - Lucas Marc Fuhrer; Nils Herger (Swiss National Bank, Study Center Gerzensee, 2022)
This paper empirically examines the effect of population growth on real interest rates. Although this effect is well founded in macroeconomic theory, the corresponding empirical results have been rather tenuous. Demographic interest rate theories are typically based on long-term relationships across generations. Accordingly, key population trends appear often only across decades, if not centuries, worth of data. To capture these trends, we distinguish between population growth resulting from a birth surplus and net migration. Within a panel covering 12 countries and the years since 1820, we find robust evidence that the birth surplus significantly affects the real interest rate.
Keywords: E43; E52; J11; 330; demographics; demographic transition; population growth; real interest rate